RESEARCH OF EFFICIENCY OF DECREASEREDUCTION OF THE DUST CONTENT IN WORKING ZONE OF jetfraction CHAMBERS - V.G. Lebedenko (Advanced Engineering Research, 2008)
The model of process of decrease of pollution of the air environment, and also technique and results of experimental researches of efficiency of process of clearing of air for jetfraction chambers is resulted.